Islamic Entrepreneurship: The Moderating Role of Eudaimonic Well-Being in MSMES Resilience Capacity During Covid-19 Pandemic - Susanti, Vitria; Zuliansyah, A.; Normasyhuri, Khavid (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
All countries in the world have been affected tremendously by the Covid-19 pandemic. As a developing country, Indonesia has also experienced dramatic changes in the political and economic environment in response to the global crisis from the corona virus. It is apparent that the pandemic lockdown caused many businesses to struggle. This paper aims to examine the influence of Islamic entrepreneurship and Eudaimonic well-being to MSMEs resilience capacity during the COVID-19. The research is done with a quantitative study with 100 MSMEs in Lampung Province, Indonesia. The main data in this study is gathered through questionnaires which then analysed by using Partial Least Square (PLS analysis). This paper found the R² value for Islamic entrepreneurship is 62.5% (high), Meanwhile, the R² for Eudaimonic Well-being is 60% (high) indicating MSMEs Resilience Capacity can be moderately explained by Eudaimonic Well-being.